Digital activism and environmental justice: Social media mobilization against waste management - Gumelar, Rangga Galura; Mukhroman, Iman; Hafiar, Hanny (Faculty of Communication Sciences Universitas Padjadjaran, 2026)
Background: Digital activism has increasingly shaped environmental justice movements, particularly in Global South contexts where local communities face environmental risks from large scale waste management projects. Social media platforms provide new spaces for grassroots mobilization, enabling citizens to circulate information, construct collective narratives, and attract broader public attention. However, empirical evidence on how digital activism amplifies environmental justice claims in localized environmental conflicts remains limited. Purpose: This study examines how social media activism mobilizes public engagement and strengthens environmental justice narratives in community resistance to waste management infrastructure. Methods: This research employs a mixed-methods approach combining quantitative content analysis and qualitative inquiry. The dataset consists of 61 Instagram posts and 175 TikTok videos related to the environmental conflict. Engagement rates (ER) were calculated to measure audience interaction, while digital observation and in-depth interviews with three key informants provided contextual insights. The analysis is informed by Schlosberg’s environmental justice framework and mediatization theory. Results: The findings indicate that visual protest narratives significantly increase engagement and narrative diffusion. A viral TikTok video depicting residents’ protests generated the highest engagement rate of 67%, significantly boosting the visibility of the campaign hashtag. Posts using symbolic protest narratives produced up to 1.8 times more social sharing compared to purely informational posts, demonstrating the importance of visual storytelling in amplifying grassroots environmental claims. Conclusion: Social media platforms function not only as communication channels but also as strategic arenas for environmental advocacy and mobilization. Implications: Digital activism can strengthen environmental justice movements by expanding citizen participation, increasing visibility of local environmental conflicts, and generating broader public pressure for more equitable environmental governance.